Enquêter sur la prostitution en Algérie. Souvenirs de Bou-Saâda - Ferhati Barkahoum (L’Année du Maghreb)
Several seminars were recently held in Algeria on issues relating to sexuality, women and the status of families. Faced with a situation that tends to encourage the confinement of women’s bodies and control their sexuality, several social practices seem to break away from such standards. Based on personal experience as a researcher working on the margins, the social phenomena of the “tribal” prostitution of the Ouled Naïl in the Algerian Sahara, this field survey explores borders and taboos (prostitution, female celibacy), and some moral uncertainties concerning post-colonial society in Algeria.